2017
DOI: 10.3389/fpsyg.2017.01663
|View full text |Cite
|
Sign up to set email alerts
|

Robots As Intentional Agents: Using Neuroscientific Methods to Make Robots Appear More Social

Abstract: Robots are increasingly envisaged as our future cohabitants. However, while considerable progress has been made in recent years in terms of their technological realization, the ability of robots to interact with humans in an intuitive and social way is still quite limited. An important challenge for social robotics is to determine how to design robots that can perceive the user’s needs, feelings, and intentions, and adapt to users over a broad range of cognitive abilities. It is conceivable that if robots were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
184
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 232 publications
(212 citation statements)
references
References 266 publications
14
184
0
2
Order By: Relevance
“…After observing the behavior of the robot in a sequence of three P R E P R I N T photographs, participants were asked to rate if the behavior of the robot was motivated by a mechanical cause or by a mentalistic reason. Results showed that participants had a preference for mechanistic explanations, as has been presented previously in the literature ( [6], [18], [13]). Interestingly, in some scenarios people tended to explain the behavior of iCub in mentalistic terms.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…After observing the behavior of the robot in a sequence of three P R E P R I N T photographs, participants were asked to rate if the behavior of the robot was motivated by a mechanical cause or by a mentalistic reason. Results showed that participants had a preference for mechanistic explanations, as has been presented previously in the literature ( [6], [18], [13]). Interestingly, in some scenarios people tended to explain the behavior of iCub in mentalistic terms.…”
Section: Introductionsupporting
confidence: 75%
“…More recently, particular interest has been driven towards how and when humanoid robots evoke mentalistic explanations of behavior [11][12][13][14]. Research with this type of robots is crucial as those share the most physical features and behavior with human agents and also because these robots would be the first ones that will interact with people in social contexts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mind perception has been shown to influence prosocial behaviors (Bering & Johnson, 2005;Epley, Waytz, Akalis, & Cacioppo, 2008;Graham & Haidt, 2010;Gray, Young, & Waytz, 2012;Shariff & Norenzayan, 2007), reactions to observing negative consequences for others (Cushman, 2008;Gray & Wegner, 2008;Ohtsubo, 2007), and the motivation to perpetuate moral standards (Haley & Fessler, 2005). Similarly, attitudes and performance in interactions with nonhuman agents can be improved when the agents trigger mind perception by displaying human features or behaviors (Bennewitz, Faber, Joho, Schreiber, & Behnke, 2005;Fussell, Kiesler, Setlock, & Yew, 2008;Huang & Thomaz, 2011;Mutlu, Forlizzi, & Hodgins, 2006;Mutlu, Kanda, Forlizzi, Hodgins, & Ishiguro, 2012;Pfeiffer-Leßmann, Pfeiffer, & Wachsmuth, 2018;Sidner, Kidd, Lee, & Lesh, 2004;Staudte & Crocker, 2011;Wiese, Metta, & Wykowska, 2017;Yamazaki, Yamazaki, Burdelski, Kuno, & Fukushima, 2010). In contrast, agents not triggering mind perception negatively impact performance in social interactions (Caruana et al, 2016;Wiese et al, 2012;Wykowska et al, 2014) and fail to induce social facilitation (Bartneck, 2003;Park & Catrambone, 2007;Riether, Hegel, Wrede, & Horstmann, 2012;Woods, Dautenhahn, & Kaouri, 2005).…”
mentioning
confidence: 99%
“…The humanization of robots, or the representation of (parts) robots as humans, can have several positive effects, contributing to the successful adoption of robots by our society (Paiva, Mascarenhas, Petisca, Correia, & Alves‐Oliveira, ; Robert, ). Many scholars working with robots aim to create an autonomous human‐like robot capable of mimicking human behaviors and emotions (Admoni & Scassellati, ; Breazeal & Scassellati, ; Fong et al, ; Goodrich & Schultz, ; Mavridis, ; Oliveira et al, ; Wiese, Metta, & Wykowska, ).…”
Section: Positive Effects Of Humanization For Hrimentioning
confidence: 99%